Exploring the creation and development of political co-brand identity: A multi-case study approach. Issue 5 (11th November 2019) - Armannsdottir, Guja; Pich, Christopher; Spry, Louise
Abstract : Purpose: The creation and development of candidate-politician brands, otherwise known as political co-brands, remains an under-researched area of study. This is supported by calls for more understanding on political co-brands and how they are positioned and managed by their creators. Framed by the concepts of internal brand identity and co-branding, this paper aims to investigate how political co-brand identity is constructed and managed over time, exploring alignment between the political co-brand and political corporate party brand. Design/methodology/approach: An interpretivist revelatory multi-case study approach, using in-depth interviews, was conducted with three political co-brands (candidates-politicians) from the UK Conservative Party. The three cases represented constituencies across the UK from the North, Midlands and South of the country. The in-depth elite interviews were conducted July 2015 to September 2015. Methodological triangulation was also adopted to assess the coherency of emerging themes with online and offline materials and documents. A two-stage thematic analytical approach was used to interpret the findings. Findings: This multiple case study demonstrates how successful political co-brands create and develop identities tailored to their constituency, often distinct from the corporate political brand and developed several years before electoral success at the ballot box. In addition, this study reveals that political co-brands are dichotomous in terms of strategically managing a degree of alignment with the corporate political brand yet maintaining a degree of independence. Research limitations/implications: This study builds on limited existing concepts such as co-branding and political brand identity as a means of critical application. Existing research on co-branding remains a "relatively limited" and complex area of study and generally focuses on fictitious brands. Political brand identity remains an under-researched area. This in turn supports the development and advancement of political branding as an area of study. This paper highlights the opportunities of using the strategic approach of co-branding to help conceptualise "candidates-politicians" as political brands' which up until now, "candidate-politician brands" have been difficult to define unlike the extensive research on corporate political brands. Practical implications: This study has implications for practice too. Organisations and different typologies of political brands will be able to use this political co-brand identity framework as a diagnostic mechanism to investigate their co-brands current identity, assess alignment and make strategic changes or reposition the envisaged identity if desired. Similarly, organisations can use this framework, key dimensions and factors as a blueprint to design and build new political brands at a corporate and/or local level. Originality/value: This study has implications for brands beyond the world of politics. Brands can adopt the political co-brand identity framework developed in this study as a pragmatic tool to investigate internally created co-brand identity and explore alignment with the corporate party brand identity. In addition, this research adds to the limited research on non-fictitious co-brands and co-branding literature at large and addresses the calls for more research on brand identity in new settings.